(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
Ostomies are a surgically created (artificial) opening between a hollow viscus and the abdominal wall, which can be temporary or permanent. The preparation of an ostomy, like any surgery, is not without risk or complications. Complications are dependent on comorbidity factors such as diabetes, obesity, malnutrition, emergency surgeries, type of surgery, surgical technique, etc. which, added, implies a worse quality of life for ostomy patients. The complications of the evacuation ostomy are divided into immediate (called early or immediate postoperative or 30 days) and late (after 30 days). Among the immediate ones we have: skin irritation, ostomy ischemia, retraction (due to suture dehiscence and subsidence), stenosis (obstruction), hemorrhage, infection with suture dehiscence. Among the late complications we have: parastomal hernia, prolapse, stricture, pyoderma around the ostomy. In the study conducted the most frequent type of pathology with complication of evacuation ostomies was the 50%abdomen trauma, followed by the 30%perforrative acute abdomen and finally the obstructive20%. Colostomy necrosis was the first complication detected in 6 patients (30%), surrounding skin or dermatitis 4 (20%), ostomia 4 (20%) retraction, periostomal abscess 3 (15%), paraostomal hernia 3 (15%).